The Effect of Transformational Leadership and Knowledge Sharing on Employee Performance PBMTI Jepara: The Effect of Transformational Leadership and Knowledge Sharing on Employee Performance PBMTI Jepara - Nur Hikmah; Nur Ahmad Budi Yulianto (Institute of Computer Science (IOCS), 2020)
This research objective is to obtain the influence of the Transformational Leadership, and knowledge sharing toward the employee performance of PBMTI Jepara. There were ten research samples of employees chosen by the method of disproportionate stratified sampling. The data was collected through the quetionnaire and then analised by using SmartPLS (Partial Least Square).The analysis result prooved that the transformationalleadership, and knowledge sharing have influence toward the performance which is prooved with the t statistic value about 3.093and 6.164 which all of them have the value bigger than 1.96. It means that the variable has the influence toward the performance of employee in PBMTI Jepara. Whereas, Meanwhile, to know the influence of exogenous variable toward the performance can be seen from each determination coefficient about - 0.255 and 0.604. This points out that the variable of transformational leadership has the negative influence toward the performance, whereas the other variables have the positive influence toward the performance. Hypotesis result indicate that the hypothesis 1is weren’t provide because toward the negative influence , but the hypothesis 2 were provide and to be significant impact compare on employee performance. The Goodness of fit as the model which is used to find out the influence of exogenous variable toward endogen variable has the value of 0.792 that can be seen at R square which means those three exogenous variables have the influence about 79.2 % toward the endogenous variable of performance and the rest is 20.8% from the other factors contribution.